NAHDLATUL ULAMA DAN PENEGAKAN HAK ASASI MANUSIA DI INDONESIA - Maghfur Ahmad (Religia, 2010)
Nahdlatul Ulama (NU) as a civil power has a strategic role to control and enforce the Human Right in Indonesia. To NU, Human Right is a seedling of basic right values living in the West, Islam and Indonesia. In the context of Indonesian Human right, five basic principles: hifz al-nafs (right to live), hifz al-din (right to believe), hifz al-nasl (right to produce children), hifz al-mal (right to have property), and hifz al-aql (right to have his or her mind be safe) are understood contextually according to the local wisdom, and it, sometime, is different from the orthodox concept of Sunni. NU views the Human Right movement in Indonesia as an oppositional movement to other side, especially the government that neglects values and human basic rights. It also means the movement not to preserve the tyranny regime, but as a progressive movement to manifest the citizens’ freedom to get their human right guaranty. The struggle to enforce the Human Right, to NU, is only to manifest more prosperous, fairer, and safer national life.